Studi Kesehatan Lingkungan Terhadap Penderita Tuberkulosis Paru yang Mengkonsumsi Obat Anti Tuberkulosis (OAT) - Dewi Yudiana Shinta; Muhammad Diki Juliandi; Melly Siska Suryani; Ikhwan Resmala Sudji; Merry Thressia; Herix Sonata MS (SEHATI: Jurnal Kesehatan, 2025)
Pulmonary tuberculosis (TB) is an infectious disease that requires long-term treatment using anti-tuberculosis drugs (OAT). The use of OAT, especially in the long term, can cause side effects on metabolism and organ function, one of which is indicated by changes in uric acid and urea levels in the blood. This study aims to analyze the relationship between environmental health and uric acid and urea levels in pulmonary TB patients undergoing OAT therapy. The benefits of this research include examining the relationship between uric acid and urea levels in pulmonary TB patients taking anti-tuberculosis drugs (OAT) and informing patients that TB treatment may cause an increase in uric acid and urea levels in the kidneys. The study design is an analytical observational study. The cross-sectional design involves measuring uric acid and urea levels using a chemical analyzer. The results of uric acid level measurements using the chemical analyzer showed that 25 respondents had normal uric acid levels (72%), while 28% had levels above the normal range. For urea levels, 16 respondents (64%) had normal values, and 9 respondents (36%) had levels exceeding the normal range. After consuming OAT for 1 month or less, 9 patients (60%) were observed, 2–3 months for 2 patients (13.33%), and 5 months for 1 patient (6.67%).